Tinjauan atas Hand, Foot, and Mouth Disease - Bella Kurnia (PT. Kalbe Farma Tbk., 2020)
Hand, foot and mouth disease (HFMD) adalah infeksi enterovirus yang sering terjadi pada anak-anak di bawah 10 tahun. HFMD ditandai dengan lesi pada mulut, tangan dan kaki. HFMD pernah menjadi KLB dalam 1 dekade terakhir. HFMD sangat infeksius, biasanya ringan dan self limiting, akan tetapi dapat menimbulkan komplikasi berat.Hand, foot and mouth disease (HFMD) is an enterovirus infection commonly found in children under 10 year-old. HFMD characterized by lesion in the mouth, hand, and foot. HFMD outbreaks occur in the last decade. HFMD is very infectious but mild and self-limiting; however, there were several severe complications of HFMD.